The Influence of Workload, Work Stress, Organizational Culture, and Work Environment on Job Performance at Employees of PT. Bank Sumut Syariah Deli Serdang Area - Pratama, Ridho; Nurlaila, Nurlaila; Lathief Ilhamy Nasution, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to examine the effect of workload, work stress, organizational culture and work environment on job performance. This research was conducted at the sub-branch office of the Bank Sumut Syariah which is located in the Deli Serdang area, namely in Lubuk Pakam, Limau Manis, and Hamparan Perak. Researchers took the entire population with a total of 35 people as research respondents. This research method uses quantitative research using an associative approach, data collection techniques using a questionnaire. The data obtained were analyzed using the multiple linear regression method. The results showed that workload had a positive and significant effect on job performance. It can be seen from the results of data processing the Workload variable tvalue 2.374 > ttable 2.042. As for the variables Work Stress, 2.042, Organizational Culture variable value of 1.069 < ttable 2.042, t value the Work Environment variable is 0.783 < ttable 2.042. The results of the simultaneous test hypothesis show that Workload, Work Stress, Organizational Culture and Work Environment simultaneously affect Job Performance. This can be seen from the calculated Fvalue of 3.908 > Ftable 2.68.